2021
DOI: 10.1002/slct.202101035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Anticancer Activities of New 1,4‐Disubstituted‐1,2,3‐triazoles Derivatives through Click Approach

Abstract: The synthesis of a new series 1-(3-methoxy-4-((1-phenyl-1H-1,2,3-triazole-4-yl)methoxy) phenyl)ethanone via click chemistry approach utilizing azide-alkyne cycloaddition reactions is reported in this study. The structures of all newly synthesized compounds were analyzed by IR, NMR, and Mass spectral techniques. All the newly synthesized compounds were subjected to cytotoxicity assay against a panel of three human cancer cell lines (HepG2, A549, and MCF-7) using 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The plausible mechanism is framed (Figure ) based on the combination of experimental results and DFT calculations for the cycloaddition reaction of epoxide and CO 2 to form propylene carbonate (PC) with their interacting bond distances. The said mechanism is well corroborated with previous reports from other groups. ,, …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The plausible mechanism is framed (Figure ) based on the combination of experimental results and DFT calculations for the cycloaddition reaction of epoxide and CO 2 to form propylene carbonate (PC) with their interacting bond distances. The said mechanism is well corroborated with previous reports from other groups. ,, …”
Section: Resultssupporting
confidence: 92%
“…35 The infrared (IR) spectrum of compounds (ZnMOF1 and ZnMOF2) indicates the formation of the product as it shows the characteristic absorption peaks at 1453, 1451 and 1404, 1400 cm −1 which correspond to the N−N and NN stretching, respectively. 50 The peaks at position 542, 437 cm −1 (for ZnMOF1) and 557, 440 cm −1 (for ZnMOF2) are attributed to Zn−O and Zn−N stretching vibration. 44 Crystal Å for ZnMOF2 (Figure S1) and in assistance of the monodentate carboxyl groups of two (L) 2− ligands joined two Zn1 and Zn2 ions to form a remarkable 14-membered planar macrocycle (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compound 60 exhibited potent anticancer activity against HepG2, A549 and MCF-7 cell lines with IC50 value of 3.42 µM, 1.26 µM and 5.96 µM, respectively, among synthesized 1,2,3-triazole derivatives reported by Nipate et al [78] using click reaction. Azab et al [79] reported in vitro antitumor screening of novel series of 1,2,3-triazole-containing hybrids synthesized via CuAAC reaction.…”
Section: Antitubercular Activitymentioning
confidence: 95%
“…[26] 1,2,3-Triazole scaffold represents the important class of heterocycle containing a wide range of medicinal activities including anti-in ammatory, antimicrobial, ant, tuberculosis, antiplatelet, anticancer, and antiviral activity. [27][28][29][30][31] Owing to the signi cant features of nitrogen and oxygen-containing heterocycles to modulate the physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%